Food poisoning, policy, and politics : corned beef and typhoid in Britain in the 1960s - Smith, David F., 1954- (Boydell Press, 2005)
"Study of the 1963/4 typhoid outbreak, highlighting issues and debates which are strikingly relevant today"--Provided by publisher